Kebijakan Ekonomi Publik Intervensi Pemerintah terhadap Eksternalitas dan Ketimpangan Pendapatan - Fiola Surya Dwi Fahmi; Hendra Riofita (Pusat Riset dan Inovasi Nasional, 2025)
Public economic policy is a crucial instrument in addressing various forms of market failure, such as negative externalities and income inequality. In this context, government intervention through taxation, subsidies, and redistribution serves as a strategic step to achieve a balance between economic efficiency and social equity. This article aims to examine the role of public economic policy in correcting the impact of externalities and reducing the gap in income distribution. Using a qualitative descriptive approach and literature study method, the results show that Pigovian taxes, subsidies for positive sectors, progressive tax systems, and data-based redistribution programs are key pillars in building a fairer and more inclusive economic system.